Peripheral Blood CD64 Levels Decrease in Crohn's Disease following Granulocyte and Monocyte Adsorptive Apheresis - Chiba, Toshimi (S. Karger AG, 2011)
Granulocyte and monocyte adsorptive apheresis (GMA) is reportedly useful as induction therapy for Crohn's disease (CD). However, the effects of GMA on CD64 have not been well characterized. We report here our assessment of CD64 expression on neutrophils before and after treatment with GMA in two patients with CD. The severity of CD was assessed with the CD activity index (CDAI). The duration of each GMA session was 60 min at a flow rate of 30 ml/min as per protocol. CD64 expression on neutrophils was measured by analyzing whole blood with a FACScan flow cytometer. In case 1, CD64 levels after each session of GMA tended to decrease compared to pretreatment levels, whereas in case 2, CD64 levels dropped significantly after treatment. The CDAI decreased after GMA in both cases 1 and 2. A significant correlation was noted between CDAI scores and CD64 levels in both cases. In conclusion, GMA reduced blood CD64 levels, which would be an important factor for the decrease of CDAI scores.